Computational Modelling of Selective Capture Mechanisms in Conduction System Pacing - Mohammadreza Kariman; Matthias A. F. Gsell; Edward J. Vigmond; Aurel Neic; Christoph M. Augustin; Gernot Plank (Annals of Biomedical Engineering, 2026)
Purpose Conduction system pacing (CSP) is gaining clinical significance owing to its ability to restore a physiological activation sequence in the ventricles. Whilst His bundle pacing producing the most physiological activation is preferable, due to implant complications the selective activation of the left bundle branch (LBB) by LBB area pacing is considered an alternative, offering both a simpler implant and a physiological activation sequence. However, the physical mechanisms facilitating selective activation of the LBB remain poorly understood. Methods We developed a structurally and biophysically detailed computer model of the interventricular septum and LBB to quantitatively elucidate the role of lead position, orientation and polarity in achieving optimal selective left bundle branch pacing (LBBP) thresholds, using a geometrically detailed model of a clinically widely used CSP lead. Results A deep implant within the left ventricular subendocardium ensuring a direct contact between electrode and LBB is key for effective selective LBBP. For low strength, selective LBBP is feasible, but capturing the LBB in its entirety could only be achieved using higher strengths that led to non-selective LBBP. Switching the tip polarity to anodal was not beneficial, requiring higher strengths to activate the LBB. Lead orientation relative to the LBB bundles was found to influence the selective LBBP capture threshold and the number of synchronously activating bundles. Conclusion The model explains the impedance trends that are clinically observed when advancing the tip through the interventricular septum into the LBB region, as well as sudden impedance drops associated with implant complications such as septal perforation or lead dislodgement. Quantitative consistency with clinically observed trends supports model credibility, and indicates that simulation may offer an effective approach for guiding the design of improved CSP leads, facilitating a selective and synchronous activation of the entire LBB.